2015
DOI: 10.1080/10402381.2014.998397
|View full text |Cite
|
Sign up to set email alerts
|

Property owner beliefs and goals related to shoreline maintenance behaviors

Abstract: Individual differences in shoreline maintenance behaviors are likely partially attributable to individual differences in relevant beliefs and goals. Lake property owners can help reduce the impact of development by maintaining a vegetated buffer on their shoreline, as opposed to grooming an expansive manicured lawn. A survey mailed to residential lake property owners in Wisconsin (n returned = 155, response rate = 64%) measured lake-specific beliefs and goals and self-reported frequency of engaging in 4 behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Developed lakes have less CWH due to direct removal and loss of riparian forests, with potential impacts lasting decades due to slow natural replacement (Amato et al, 2015; Elias & Meyer, 2003; Francis & Schindler, 2006; Marburg et al, 2006, 2009). We documented a significant negative lake‐level effect of LRD on CWH (see Marburg et al, 2006 for a more detailed treatment of this CWH data set).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developed lakes have less CWH due to direct removal and loss of riparian forests, with potential impacts lasting decades due to slow natural replacement (Amato et al, 2015; Elias & Meyer, 2003; Francis & Schindler, 2006; Marburg et al, 2006, 2009). We documented a significant negative lake‐level effect of LRD on CWH (see Marburg et al, 2006 for a more detailed treatment of this CWH data set).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that developed lakes have decreased macrophyte abundances (Radomski, 2006; Radomski & Goeman, 2001). Developed lakes also tend to have less CWH, largely due to removal by shoreline property owners (Amato et al, 2015; Jorgensen et al, 2006). This loss of CWH as predation refugia in the littoral zone can destabilize predator–prey dynamics and lead to reductions in prey fish abundance (Gaeta et al, 2014; Helmus & Sass, 2008; Sass, Kitchell, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social indicators framework used in this paper (Genskow and Prokopy ) reflects substantial literature on factors influencing the adoption of conservation practices in agricultural settings (e.g., Nowak ; Lambert et al ; Prokopy et al ), riparian/lakeshore settings (e.g., Amato et al ; Shaw et al ), and urban areas (Brehm et al ). The context in which NPS outreach activities are conducted is critical for interpreting and acting upon evaluative information (Stough‐Hunter et al ; Thurston et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, some property owners feel that native vegetation and woody habitat impede recreation, raise safety concerns, and block views of the lake (Jorgensen et al, 2005). Lakefront property owner beliefs about the ability of lakes to withstand shoreline modification, benefit from conservation actions, and the consequences of shoreline development have been reported to be important predictors of conservation actions (Amato et al, 2015;Jorgensen & Stedman, 2006;Shaw et al, 2011). However, the same relationship was not found for formal education (Welle & Hodgson, 2011), potentially because formal education does not necessarily include lessons in ecology.…”
Section: Introductionmentioning
confidence: 99%